Chronic obstructive pulmonary disease burden, grades and erythrocytosis at a tertiary hospital in western Uganda - Banturaki, Amon; Munyambalu, Dalton Kambale; Kajoba, Dickson; Onchoke, Verah Bella; Peris, Alina; Ryamugwiza, Prosper; Amandua, Jacinto; Akaba, Kingsley (BioMed Central Ltd, 2024)
Background Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide among people over 40 years of age, and erythrocytosis is one of the major complications associated with increased mortality among COPD patients. The study aimed to determine the proportion of COPD, associated factors, and the burden of erythrocytosis among COPD participants. Methods and materials A descriptive cross-sectional study design was used. A consecutive sampling technique was used to obtain study participants at the Fort Portal Regional Referral Hospital outpatient clinic. Focused history and physical examination were carried out to select eligible participants. Participants were screened using the COPD population screener for spirometry after consenting to participate. The study enrolled all adults at risk of having COPD based on the COPD population screener and able to undergo spirometry. Spirometry was carried out according to the Global Chronic Obstructive Lung Disease and European Respiratory Society guidelines, and haemoglobin concentration was measured. Results One hundred eighty participants were enrolled in the study, most of whom were females. The modal and mean age of participants was 60 years with 139 (77.2%) females and primary as the highest education level 149(82.8%). The proportion of COPD was 25% (45) [95% CI 18.9 – 32] and highest among females (68.9%) and those aged 60 years and above (70%). The combined COPD assessment tool groups had a proportion of 55.6%, 37.8%, 4.4%, and 2.2% for groups A, B, C, and D, respectively. Age<50 years was protective against COPD, while for every additional year of smoking, there was an associated 6.5% increased risk compared to the general population. Additionally, the proportion of erythrocytosis among COPD participants was 6.7%. Conclusions and recommendations There was a high proportion of COPD among study participants (25%), with a 6.7% proportion of erythrocytosis. We recommend a complete blood count for every patient in groups C and D of the ABCD COPD GOLD groups. Keywords Chronic obstructive pulmonary disease, Erythrocytosis, Biomass fuel, Smoking
Keywords: Chronic obstructive pulmonary disease, Erythrocytosis, Biomass fuel, Smoking